2002
DOI: 10.1093/oxfordjournals.intqhc.a002611
|View full text |Cite
|
Sign up to set email alerts
|

Using an explicit guideline-based criterion and implicit review to assess antipsychotic dosing performance for schizophrenia

Abstract: The explicit antipsychotic dose criterion may provide a useful and efficient screen to identify patients at significant risk for quality of care problems; however, the relatively low specificity suggests that the measure may not be appropriate for quality measurement programs that compare performance among health plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The overestimation of inappropriate care using explicit criterion found in this study is similar to other studies assessing appropriateness of processes of care [33,41]. In the only other study comparing explicit and implicit review in mental health, Owen et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The overestimation of inappropriate care using explicit criterion found in this study is similar to other studies assessing appropriateness of processes of care [33,41]. In the only other study comparing explicit and implicit review in mental health, Owen et al.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the review instrument developed by Owen et al. (for assessing appropriateness of antipsychotic dose), a 4‐point scale rating the appropriateness of combination antipsychotic treatment was used initially [33]. The rating form was piloted by a psychiatrist and a mental health pharmacist with six medication summaries.…”
Section: Methodsmentioning
confidence: 99%
“…There are several appropriate reasons for variation from guideline dose recommendations, and half or more of patients prescribed out-ofrange doses may actually be receiving appropriate care. 35 Two studies based on data from the mid-to late-1990s reported similarly high rates of guideline-concordant dosing for schizophrenia, 4,36 rates substantially higher than the 50 -60% rates of guideline concordant dosing reported earlier. 37,38 This apparent increase in guideline-concordant dosing may have resulted from increasing awareness among psychiatrists that evidence-based guidelines recommended antipsychotic doses within a moderate range.…”
Section: Discussionmentioning
confidence: 92%
“…However, while many guidelines and recommendations for the pharmacologic treatment of schizophrenia have been developed in recent years (Lehman and Steinwachs 1998a;Lehman et al 2004;APA 1997;Chiles et al 1999;McEvoy et al 1996), studies that have evaluated adherence to them in actual practice have shown substantial rates of non-adherence (Chen et al 2000), including frequent use of dosages both higher (Walkup et al 2000; Leslie and Rosenheck (2001) and lower (Owen et al 2002) than the recommended ranges, delays in implementing the guidelines (Valenstein et al 2001), or failure to change antipsychotic medications when guidelines would suggest that such changes are indicated (Sernyak et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been demonstrated that deviations from practice recommendations may be appropriate on chart review (Owen et al 2002), there have been no efforts to directly solicit the opinions of the prescribing clinicians with regards to case-specific guideline deviations. The current study was designed to investigate the clinical rationales for a commonly identified deviation from antipsychotic prescribing practices-prescribing higher than recommended dosages of antipsychotics.…”
Section: Introductionmentioning
confidence: 99%